Analisa Pengaruh Ekonomi Kerakyatan sesuai Amanat UUD 1945 terhadap Pertumbuhan Ekonomi Indonesia - Hendri Hartono; Rido Sarwono (Binus Business Review, 2011)
Cooperatives are one ideological concept of Indonesian economy and stated firmly in constitutional of Republik Indonesia. The growth of cooperatives in Indonesia has complex problems so they are pushed by capitalism power from private companies. Whereas, cooperatives were built as economical blocks in mediating Indonesian people to be more welfare economically. Data from Cooperatives Department, there are significant growth of cooperatives from 2006 to 2010: the active cooperatives are 98.944 up to 124.855. Meanwhile, the unactive cooperatives are 42.382 (2006) to 52.627 (2010, in total amount of 177.482 in 2010. The cooperatives growth is interesting to be research in the future to identify wealth of cooperatives and which area has the most rapid growing of cooperatives.